Fertility of Vriesea gigantea Gaud. (Bromeliaceae) in southern Brazil1 - Paggi, Gecele M; Palma-Silva, Clarisse; Silveira, Lucas C T; Kaltchuk-Santos, Eliane (American journal of botany, 2007)
Plant fertility is a central subject of many questions in plant evolutionary and conservation biology. Pollen availability, abiotic resources, and flowering pattern can limit fruit and seed production. Open pollination and pollen supplementation studies are used to estimate any pollen limitation in natural populations. To study the impact of these factors on the reproductive success of Vriesea gigantea, an epiphytic bromeliad in the Atlantic Rainforest in Brazil, its fertility in four natural populations in Itapua State Park was assessed by considering plant and inflorescence size, flower production, fruit and seed set, flower and fruit set pattern, and seed viability and germination rate. Supplemental pollination in adult plants was used to determine whether fruit production in V. gigantea is limited by reception of pollen. The results showed that V. gigantea has a high production of flowers, fruits, and seeds. Seeds are highly viable in all populations, presenting an average germination rate of 94% (SE ± 3.5). Plants of V. gigantea from Itapua State Park are highly fertile. The high proportion of fruit and seed set after manual hand pollination indicates that the species is self-compatible. Pollination treatments showed evidence of pollinator limitation in the Itapuä State Park population. [PUBLICATION ABSTRACT]